Imaging techniques in plant transport: meeting review - Fricker, M; Oparka, K (1999)
This review covers recent advances in imaging techniques that were presented during the 11th International Workshop on Plant Membrane Biology, Cambridge, August 1998. Cell biology has been revolutionized by the arrival of green fluorescent protein (GFP) and GFP is now routinely used as a cell-lineage marker in plants, to localize proteins to subcellular compartments or as a tag to follow dynamics in endo-membrane compartments. More recent developments include modification of GFP to form physiological sensors for calcium and pH. These provide a transgenic approach in parallel with conventional chemical dyes to track signalling events or follow membrane recycling pathways. Confocal microscopy has become a routine technique to visualize these fluorescent probes, particularly in intact tissues. Multi-photon microscopy may push the capability of imaging techniques further, allowing imaging at even greater depths and long-(red)-excitation of UV fluorochromes. The luminescent calcium indicator, aequorin, has been much more extensively used in plants than the transgenic fluorescent calcium indicators, and photon-counting imaging systems can now record calcium transients at video-rate in intact plants. Digital imaging, whether camera, confocal or multi-photon, provides quantitative data, but correct interpretation requires rigorous analysis of noisy and partially correlated imaging data. Statistical analysis by Bayesian inference may well become the most appropriate technique to handle such images, but has only recently been applied to ratio imaging in plants. In addition to generating images, light can also be used to manipulate intracellular events using photolysis of caged probes. The control of the location, timing and amplitude of the release allows exquisitely subtle manipulation of signalling networks. More aggressive pulses of UV laser-light provide an equally powerful tool either to ablate whole cells completely for developmental studies or to punch-out tiny holes in the cell wall to give access to the plasma membrane for patch-clamping and electrophysiological investigation of cells in situ.